Implementasi Metode Bernyanyi dalam Meningkatkan Kosa Kata Bahasa Arab Pada Anak Usia Dini di TK Bunda Harapan - Dwi Binti Masfufah; Jami’atunnur (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study aims to describe the implementation of the singing method in improving Arabic vocabulary mastery in early childhood at Bunda Harapan Kindergarten Bengkalis. The singing method was chosen because it suits the characteristics of early childhood people who are active, enjoy playing, and learn easily through fun activities. This study uses a qualitative approach with a descriptive research type. Data were collected through participatory observation, semi-structured interviews with teachers and parents at Bunda Harapan Kindergarten, Bengkalis. Data analysis was carried out through reduction, presentation, and inductive conclusion drawing. The results showed that the implementation of the singing method routinely and planned can improve Arabic vocabulary in early childhood. The songs taught are adapted to learning themes such as numbers, animal names, body parts, and the universe. Singing activities accompanied by music, movement, and video media make the learning atmosphere more interactive, fun, and effective. This method also improves children's pronunciation skills, activeness, and confidence in speaking Arabic. Thus, the singing method has proven to be an innovative and effective learning strategy in introducing and enriching Arabic vocabulary for early childhood while fostering their motivation and love for Arabic from an early age.